2007
DOI: 10.1074/jbc.m703876200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intra-organellar Chaperone Capacity for Dealing with Stress-induced Protein Unfolding

Abstract: Molecular chaperones are essential for cells to prevent that partially unfolded proteins form non-functional, toxic aggregates. This requirement is increased when cells experience protein unfolding stresses and such could affect all compartments in the eukaryotic cell. Whether all organelles are equipped with comparable chaperone capacities is largely unknown, mainly due to the lack of suitable reporters that allow such a comparison. Here we describe the development of fluorescent luciferase reporters that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 57 publications
5
39
0
Order By: Relevance
“…It has been suggested that intranuclear inclusion formation of polyQ-expanded ATXN3 is promoted by the nuclear environment (11), and in fact, heat-induced denaturation of proteins is more rapid in the nuclear compartment compared with the cytoplasm, as demonstrated by biophysical (28) and biochemical (29,30) experiments. On the other hand, evidence has been provided that nuclear inclusions are active proteolytic centers (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that intranuclear inclusion formation of polyQ-expanded ATXN3 is promoted by the nuclear environment (11), and in fact, heat-induced denaturation of proteins is more rapid in the nuclear compartment compared with the cytoplasm, as demonstrated by biophysical (28) and biochemical (29,30) experiments. On the other hand, evidence has been provided that nuclear inclusions are active proteolytic centers (31).…”
Section: Discussionmentioning
confidence: 99%
“…HSPA1A is a member of the Hsp70 family (30). In cooperation with other chaperones, HSPA1A mediates the folding of newly translated polypeptides in the cytosol, as well as within organelles (31).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to two reasons; either the nuclear environment is highly dense and crowded with macromolecules which enhances the sensitivity of the Fluc variants to stress and/or, this can be due to the differences in the proteostasis capacity to deal with unfolded proteins. Indeed, it has been shown in past by many studies that the nuclear proteome is highly sensitive to stress and that nuclear damage following protein misfolding stress plays a very critical role in stress induced cell death (Hageman et al, 2007;Michels et al, 1997;Michels et al, 1995).…”
Section: Vi6 Analysis Of Intra-compartmental Proteostasis Capacity mentioning
confidence: 99%